The fiscal impact of immigration in the EU - Michael Christl; Alain Bélanger; Alessandra Conte; Jacopo Mazza; Edlira Narazani (European Commission, Joint Research Centre (JRC), 2021)
The increasing flows of immigrants in Europe over the last decade has generated a range of considerations in the policy agenda of many receiving countries. One of the main considerations for policy makers and public opinions alike is whether immigrants contribute their "fair" share to their host country tax and welfare system. This paper seeks to answer this question based on an empirical assessment of the net fiscal contributions of immigrants in the 27 EU member states using EUROMOD, a EU-wide tax-benefit microsimulation model. In addition to the traditional view of the tax-benefit system, we add indirect taxation and in-kind benefits to the analysis of net contributions. Our findings highlight that migrants on average contributed about 250 euro per year more than natives to the welfare state in 2015. However, when we take an average age-specific life-cycle perspective, we find that natives generally show a higher net fiscal contribution than both, intra-EU and extra-EU migrants, while extra-EU migrants contribute on average less than intra-EU migrants.
Keywords: J15; H2; H5; 330; Migration; Microsimulation; Tax-benefit; system; EUROMOD